Thermoregulatory consequences of salt loading in the lizard Pogona vitticeps - Scarpellini, Carolina da Silveira [UNESP]; Bicego, Kenia C. [UNESP]; Tattersall, Glenn J. (Company Of Biologists Ltd, 2015)
Previous research has demonstrated that dehydration increases the threshold temperature for panting and decreases the thermal preference of lizards. Conversely, it is unknown whether thermoregulatory responses such as shuttling and gaping are similarly influenced. Shuttling, as an active behavioural response, is considered one of the most effective thermoregulatory behaviours, whereas gaping has been proposed to be involved in preventing brain over-heating in lizards. In this study we examined the effect of salt loading, a proxy for increased plasma osmolality, on shuttling and gaping in Pogona vitticeps. Then, we determined the upper and lower escape ambient temperatures (UETa and LETa), the percentage of time spent gaping, the metabolic rate ((V) over dot(O2)), the evaporative water loss (EWL) during gaping and non-gaping intervals and the evaporative effectiveness (EWL/(V) over dot(O2)) of gaping. All experiments were performed under isotonic (154 mmol l(-1)) and hypertonic saline injections (625, 1250 or 2500 mmol l(-1)). Only the highest concentration of hypertonic saline altered the UETa and LETa, but this effect appeared to be the result of diminishing the animal's propensity to move, instead of any direct reduction in thermoregulatory set-points. Nevertheless, the percentage of time spent gaping was proportionally reduced according to the saline concentration; (V) over dot(O2) was also decreased after salt loading. Thermographic images revealed lower head than body surface temperatures during gaping; however this difference was inhibited after salt loading. Our data suggest that EWL/(V) over dot(O2) is raised during gaping, possibly contributing to an increase in heat transfer away from the lizard, and playing a role in head or brain cooling.
Keywords: Gaping; Shuttling; Metabolic rate; Evaporative water loss; Brain cooling